Jeremiah Kirby, author of 'Farriery' in the 1806-1823 editions of the Encyclopaedia Britannica - Molony, V.; Warwick, Colin M (The Veterinary History Society, 2013)
This entry on 'Farriery' in the Encyclopaedia Britannica is a 155 page review of veterinary medicine, written in 1806. It includes: Introduction; Part 1 History; Part II Structure of the Horse; Part III Operations performed on Domestic Animals; Part IV Means of preserving the health of Domestic Animals; Part V Veterinary Materia Medica; Part VI Diseases incident to Domestic Animals; an Index and 6 Plates with 20 Figures. It was first published in Volume 8 part 2 of the 4th Edition (1806) and was also included in the 5th and 6th Editions of the Encyclopaedia Britannica. This review was a source reference for Sir Frederick Smith in his History of Veterinary Literature! and he attributed it to John Lawrence, but he had reservations and did not include it in his list of John Lawrence's works. The quality of the review, the clear, concise presentation, breadth and scholarly acknowledgement of the works of more than 34 authors, including Delabere Blaine (named in the text 80 times), John Lawrence (53 times), Edward Coleman (43 times), John Feron (36 times) and James Clark (30 times), indicated that it was written by someone who was familiar with the work of contemporary veterinary writers. It also appeared from the text that the author was familiar with Scotland because of references to places in the Lothians and Borders. The review is likely to have been used, by many members of the veterinary profession including William Dick (1793-1866), but does not appear to have been acknowledged by veterinary writers of the time. This may have been due to reluctance or the inability of its author to publicise his work, in contrast to many other veterinary writers at that time. After a long search for the author, he was found, by chance, in the preface of the 5th Edition, an obvious place with the benefit of hindsight.
Keywords: veterinary history